Wiedza czynnikiem konkurencyjności przedsiębiorstw - ujecie retrospektywne - Jabłoński, Marek (Knowledge as the determinant of competitive ddvantage of enterprises - retrospective approach, 2006)
The article presents the concept of knowledge as the determinant of competitive advantage of an enterprise. It shows different meaning of knowledge in particular types of organization i.c. taylorian. human relations, humanized and modern organization. The paper stresses fuzzy characteristics of knowledge of the modern organization. The final part of the article points out the broad and narrow meaning of knowledge.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 114-123